Reverse apprenticeship: Imagine the student as teacher. Issue 3 (2nd July 2020) - Rothberg, Brian; Chavez, Alexis
Abstract: The training of psychiatrists doesn't end with medical school, residency or fellowship, but instead requires life-long learning. Over long careers, psychiatrists must remain flexible and curious to procure further knowledge and confront deep biases. Sometimes, in the course of learning, psychiatrists may find themselves taught by their students. This paper describes the striking example of how a psychiatric resident was able to help her supervisor provide group psychotherapy for a transgender patient population about which he was naïve and she had particular knowledge, as well as both of them learning from group members in the process.